European protocols for the diagnosis and initial treatment of interstitial lung disease in children. Issue 11 (1st July 2015) - Bush, Andrew; Cunningham, Steve; de Blic, Jacques; Barbato, Angelo; Clement, Annick; Epaud, Ralph; Hengst, Meike; Kiper, Nural; Nicholson, Andrew G; Wetzke, Martin; Snijders, Deborah; Schwerk, Nicolaus; et al.
Abstract : Interstitial lung disease in children (chILD) is rare, and most centres will only see a few cases/year. There are numerous possible underlying diagnoses, with specific and non-specific treatment possibilities. The chILD-EU collaboration has brought together centres from across Europe to advance understanding of these considerations, and as part of this process, has created standard operating procedures and protocols for the investigation of chILD. Where established consensus documents exist already, for example, for the performance of bronchoalveolar lavage and processing of lung biopsies, these have been adopted. This manuscript reports our proposals for a staged investigation of chILD, starting from when the condition is suspected to defining the diagnosis, using pathways dependent on the clinical condition and the degree of illness of the child. These include the performance of genetic testing, echocardiography, high-resolution CT, bronchoscopy when appropriate and the definitive investigation of lung biopsy, in order to establish a precise diagnosis. Since no randomised controlled trials of treatment have ever been performed, we also report a Delphi consensus process to try to harmonise treatment protocols such as the use of intravenous and oral corticosteroids, and add-on therapies such as hydroxychloroquine and azithromycin. The aim is not to dictate to clinicians when a therapeutic trial should be performed, but to offer the possibility to collaborators of having a unified approach when a decision to treat has been made.